Excessively delayed maternal reaction after their perception of decreased fetal movements in stillbirths: Population-based study in Japan. Issue 6 (December 2017) - Koshida, Shigeki; Ono, Tetsuo; Tsuji, Shunichiro; Murakami, Takashi; Arima, Hisatomi; Takahashi, Kentaro
Abstract: Background: Fetal movement is the most common method to evaluate fetal well-being. Furthermore, maternal perception of decreased fetal movements is associated with perinatal demise. Previously, we showed that perception of decreased fetal movements was the most common reason for mothers visiting the outpatient department among those who had stillbirths in our region. Further investigation of stillbirths with decreased fetal movements is essential to find a possible way of preventing stillbirth. Aim: To investigate maternal reaction time after their perceiving decreased fetal movements among stillbirths in our region of Japan. Methods: This is a population-based study of stillbirths in Shiga Prefecture, Japan conducted from 2007 to 2011. We sent a questionnaire to each obstetrician who had submitted the stillbirth certificate. We reviewed and evaluated the questionnaires returned from the obstetricians. Findings: There were 66 cases (35%) with decreased fetal movements among 188 stillbirths in Shiga during the study period. The number of maternal visits to outpatient department after perception of decreased fetal movements within 24 h was only seven (11%) among 64 stillbirths diagnosed at outpatient department. Conclusion: We conclude that delayed maternal visit after perceiving decreased fetal movements is frequently observed in stillbirths. Promoting more thorough maternal education on fetal movements, including emphasizing earlier visitation after perceiving decreased fetal movements, may prevent stillbirths.